The plant microtubule-associated protein AtMAP65-3/PLE is essential for cytokinetic phragmoplast function - Müller, Sabine; Smertenko, Andrei; Wagner, Vera; Heinrich, Maria; Hussey, Patrick J.; Hauser, Marie-Theres (Current Biology, 2004)
Directional cell expansion in interphase and nuclear and cell division in M-phase are mediated by four microtubule arrays, three of which are unique to plants: the interphase array, the preprophase band, and the phragmoplast. The plant microtubule-associated protein MAP65 has been identified as a key structural component in these arrays [1]. The Arabidopsis genome has nine MAP65 genes, and here we show that one, AtMAP65-3/PLE, locates only to the mitotic arrays and is essential for cytokinesis. The Arabidopsis pleiade (ple) alleles are single recessive mutations, and we show that these mutations are in the AtMAP65-3 gene. Moreover, these mutations cause C-terminal truncations that abolish microtubule binding. In the ple mutants the anaphase spindle is normal, and the cytokinetic phragmoplast can form but is distorted; not only is it wider, but the midline, the region where oppositely oriented microtubules overlap, is unusually expanded. Here we present data that demonstrate an essential role for AtMAP65-3/PLE in cytokinesis in plant cells.
Created from Fastlane, Scopus look-up